Aeromonas caviae alters the cytosolic and mitochondrial creatine kinase activities in experimentally infected silver catfish: Impairment on renal bioenergetics. (September 2017) - Baldissera, Matheus D.; Souza, Carine F.; Júnior, Guerino B.; Verdi, Camila Marina; Moreira, Karen L.S.; da Rocha, Maria Izabel U.M.; da Veiga, Marcelo L.; Santos, Roberto C.V.; Vizzotto, Bruno S.; Baldisserotto, Bernardo
Abstract: Cytosolic and mitochondrial creatine kinases (CK), through the creatine kinase-phosphocreatine (CK/PCr) system, provide a temporal and spatial energy buffer to maintain cellular energy homeostasis. However, the effects of bacterial infections on the kidney remain poorly understood and are limited only to histopathological analyses. Thus, the aim of this study was to investigate the involvement of cytosolic and mitochondrial CK activities in renal energetic homeostasis in silver catfish experimentally infected with Aeromonas caviae. Cytosolic CK activity decreased in infected animals, while mitochondrial CK activity increased compared to uninfected animals. Moreover, the activity of the sodium-potassium pump (Na +, K + -ATPase) decreased in infected animals compared to uninfected animals. Based on this evidence, it can be concluded that the inhibition of cytosolic CK activity by A. caviae causes an impairment on renal energy homeostasis through the depletion of adenosine triphosphate (ATP) levels. This contributes to the inhibition of Na +, K + -ATPase activity, although the mitochondrial CK activity acted in an attempt to restore the cytosolic ATP levels through a feedback mechanism. In summary, A. caviae infection causes a severe energetic imbalance in infected silver catfish, which may contribute to disease pathogenesis. Highlights: Creatine kinase (CK) provide a temporal and spatial energy buffer to maintain the energy homeostasis. Cytosolic CK activity decreased in animals infected by Aeromonas caviae . Mitochondrial CK activity increased in animals infected by A. caviae . Aeromonas caviae causes a severe renal energetic imbalance.